Sleep Quality and Duration Can Influence Junior Physicians' Performance in High-Level Assessments for Residency Programs - Torales, Julio; Mena-Canata, Carlos; Morínigo, Macarena; Falloon, Karen; Cantero, Matías; Gauto, Sofía; López, Nicolás; Vargas, Marcelo; O'Higgins, Marcelo; Caycho-Rodríguez, Tomás; Ventriglio, Antonio; Castaldelli-Maia, João Mauricio; Barrios, Iván; Red de Estudiantes Investigadores en Neurociencias (Sleep Science, 2025)
To assess the sleep quality and duration among junior physicians in Paraguay during the month and night prior to their assessment for entry into primary specialty medical residency programs.A self-administered survey based on the Pittsburgh Sleep Quality Index (PSQI) was distributed to junior physicians after their National Commission for Medical Residencies (Comisión Nacional de Residencias Médicas – CONAREM, in Spanish) written evaluation. The survey collected data on sleep patterns during the month and night prior to the assessment. The responses were analyzed and matched with physicians' CONAREM scores.The response rate of the survey was 66.3% (270/407 physicians). Among the participants, 150 (55.5%) reported a very poor sleep quality (PSQI > 10). Women scored significantly higher on the PSQI (p = 0.013). A significant association was found between the quality of sleep on the night prior to the CONAREM evaluation and the reported evaluation scores (F-test = 3.55, degree of freedom [df] = 3, p = 0.019). In fact, the night before the written evaluation, 215 participants (79.6%) slept for ≤ 6 hours. A linear relationship was found between the duration of sleep of physicians in the night before the CONAREM written evaluation and the total score obtained in that evaluation (r = 0.200, p < 0.001), suggesting that the more hours they slept, the higher the score they reported.The quality and duration of junior physicians' sleep the night before the high-stakes evaluation positively correlated with their performance scores. These findings highlight the importance of adequate sleep for optimal cognitive performance in high-stress situations.
Keywords: sleep quality; sleep duration; physicians; performance; clinical assessment; undergraduate medical education